2020
DOI: 10.1016/j.csbj.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Archaea, tiny helpers of land plants

Abstract: Archaea are members of most microbiomes. While archaea are highly abundant in extreme environments, they are less abundant and diverse in association with eukaryotic hosts. Nevertheless, archaea are a substantial constituent of plant-associated ecosystems in the aboveground and belowground phytobiome. Only a few studies have investigated the role of archaea in plant health and its potential symbiosis in ecosystems. This review discusses recent progress in identifying how archaea contribute to plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 59 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…The observed enhanced biomass production by archaea strain NRS 31 was attributed to a higher rate of photosynthesis, which was consistent with many prior findings for other plants (Jung et al, 2020 ). Overall, plant–archaeal interactions boosted photosynthesis and strengthened cellular processes which resulted in higher growth and yield.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed enhanced biomass production by archaea strain NRS 31 was attributed to a higher rate of photosynthesis, which was consistent with many prior findings for other plants (Jung et al, 2020 ). Overall, plant–archaeal interactions boosted photosynthesis and strengthened cellular processes which resulted in higher growth and yield.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, some species of archaea can survive in both aerobic and anaerobic environments, and this advantage allows archaea to flourish in the plant rhizosphere as it generates both aerobic and anaerobic zones (Trivedi et al, 2019 ). Among their different roles, archaea appear to have the potential to promote plant growth, improve nutrient supply, boost the defense system, and protect plants against various abiotic stresses (Im et al, 2009 ; Taffner et al, 2018 ; Alori et al, 2020 ; Jung et al, 2020 ). Recently, few studies highlighted potential interactions between archaea and plants, such as the production of indole acetic acid and siderophores, sulfur cycling (Leigh, 2000 ); phosphorus-solubilization (Yadav et al, 2015 ), enhancing plant stress responses, ammonia oxidation, and nitrogen-fixing methanogens (Leigh, 2000 ), which might be attributed to plant growth-promoting effects.…”
Section: Introductionmentioning
confidence: 99%
“…After the prokaryotes and eukaryotes, archaea have been classified as the third domain of life ( Jung et al, 2020 ). Although at lower abundance in the rhizosphere compared to bacteria and fungi, but most of the predominant archaea phyla, Euryarchaeota, Crenarchaeota, Thaumarchaeota, and Korarchaeota recovered from this study have earlier been reported as members of rhizosphere microbiome of rice, maize, and Scot pine among others ( Catão et al, 2013 , Elkins et al, 2008 , Fadiji et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the significant increases seen within Thaumarchaeota at the phylum level, AOA at the genus level, as well as in archaeal‐associated metabolic gene groups among the metagenomic reads. Studies into archaeal involvement in plant–microbe interactions have shown that not only do archaea participate in nutrient cycling but also promote growth, improve disease resistance and mitigate stress factors in plants (Jung et al ., 2020). This suggests that stored topsoil treated with (NH 4 ) 2 SO 4 to stimulate the growth of AOA populations can be used to improve soils for post‐land‐use rehabilitation.…”
Section: Discussionmentioning
confidence: 99%